A schism in the Melkite Church? The conflict surrounding the seminary of Saint Anne during the Mandate period. Issue 1 (2nd January 2021) - Kronegger, Bernhard
ABSTRACT: This paper focuses on internal developments within the Melkite Church during the Mandate period. Since 1882, the French missionary order of the White Fathers had educated Melkite priests in the seminary of Saint Anne in Jerusalem. Throughout the following decades, this had led to the formation of a new type of Melkite clergy. After the tenure of Melkite Patriarch Demetrius Qādī (1919–1925) alumni of Saint Anne held almost half of all Melkite episcopal seats. His successor Cyril IX Moghabghab (1925–1947) was critical of this development, suspecting the establishment of a 'church within the church'. This paper is a case study of how Patriarch Moghabghab acted against the Saint Anne-educated clergy in his Church and tried to gain more control over the seminary. It explores the internal conflict revealed by these incidents and analyses how the responsible dicasteries of the Holy See tried to address these disturbances. Special attention is given to the use of Orientalist stereotypes by Latin clergy. The colonial mindset of Latin dignitaries towards Eastern clergy had an impact on how the Holy See regarded the Melkite Patriarch and resolved the differences surrounding Saint Anne seminary. This examination of intra-Catholic relations on regional and transnational level was carried out through research in the archives of the Vatican.